A basic/helix–loop–helix transcription factor controls leaf shape by regulating auxin signaling in apple. Issue 6 (18th August 2020) - Hu, Da‐Gang; Wang, Nian; Wang, Dong‐Hui; Cheng, Lailiang; Wang, Yan‐Xiu; Zhao, Yu‐Wen; Ding, Jun‐Yi; Gu, Kai‐Di; Xiao, Xu; Hao, Yu‐Jin
Summary: Climate‐driven phenological change across local spatial gradients leads to leaf shape variation. At higher elevations, leaves of broadleaf species tend to become narrower, but the underlying molecular mechanism is largely unknown. In this study, a series of morphometric analyses and biochemical assays, combined with functional identification in apple, were performed. We show that the decrease in apple leaf width with increasing altitude is controlled by a basic/helix–loop–helix transcription factor (bHLH TF), MdbHLH3. The MdbHLH3 ‐overexpressing lines have a lower transcript abundance of MdPIN1 encoding an auxin efflux carrier but a higher transcript abundance of MdGH3‐2 encoding a putative auxin amido conjugate synthase, resulting in a lower free auxin concentration; feeding the transgenic leaves with exogenous auxin partially restores leaf width. MdbHLH3 transcriptionally suppresses and activates MdPIN1 and MdGH3‐2, respectively, by specifically binding to their promoters. This alters auxin homeostasis and transport, consequently leading to changes in leaf shape. These findings suggest that the bHLH TF MdbHLH3 directly modulates auxin signaling in controlling leaf shape in response to local spatial gradients in apple.